Alternative legume seeds and lamb meat quality - Lanza M.; Bella M.; Priolo A.; Pennisi P. (Advanced nutrition and feeding strategies to improve sheep and goat, 2007)
Barbaresca male lambs were divided, after weaning, into four different trials to test the use of alternative legume seeds (faba bean, peas, chickpeas) in the diets. Growth and slaughter performances and meat quality on longissimus dorsi were assessed. Faba bean in total replacement of soybean meal and cereal grains enhanced hind leg bone proportion but improved meat sensory characteristics as compared to soybean diet. Faba bean associated to carob and orange pulps produced paler meat but reduced the intensity of all meat sensory attributes. Peas diets increased meat drip losses compared to soybean diet. The diet with partial replacement of soybean meal and maize by chickpeas (C20) tended to improve average daily gain and final weight compared to total replacement (C42) and to soybean diet (SBM). Lean/bone ratio resulted higher in hind leg from lambs fed chickpea diets than in those fed soybean meal diet. Diet with the higher level of chickpea inclusion significantly enhanced C12:0, C18:2 trans C18:3 n-6, C18:2 CLA, C22:5 n-3 and the total n-3 series proportions in meat as compared to soybean diet. The proportion of C18:1 trans vaccenic acid was higher in C42 and SBM groups than in C20.
11. Seminar of the FAO-CIHEAM Sub-Network on Sheep and Goat Nutrition, 2005/09/08-10, Catania (Italy)